REVIEW OF 55 ASSOCIATION FOR SLAVIC, EAST EUROPEAN, AND EURASIAN STUDIES ANNUAL CONVENTION (AMERICAN COUNCIL OF LEARNED SOCIETIES) - Rohozha, Mariya (Ukrainian Cultural Studies, 2023)
From November 30 to December 3, 2023, the 55th Annual Congress of the Association for Slavic, East European, and Eurasian Studies (ASEEES) - the most influential in the world - was held in the city of Philadelphia, United States of America a gathering of specialists in Slavic studies and Eurasian studies.